Financial performance, company size on the timeliness of financial reporting - Agoestina Mappadang; Agustinus Miranda Wijaya; Luther Jusuf Mappadang (Annals of Management and Organization Research, 2021)
Purpose: Timeliness of corporate financial reports is a crucial factor it which affects the usefulness of information made available to stakeholders or external users, especially for investors. The aim of this study was to examine whether financial performance with profitability, company size, liquidity, leverage can affect the timeliness of financial reporting. Research methodology: A causal relationship and quantitative research methods. This population was taken from industrial manufacturing companies listed on the Indonesia Stock Exchange. The total samples of this study are 30 manufacturing companies from the year 2016 to 2019. This research obtains 84 observation data and uses purposive sampling as a method to get the samples. The statistical with logistic regression for data analysis, used for this research method. Result: We found in this research that profitability, company size, liquidity, and leverage have no significant effect on the timeliness of financial reporting. Limitation: This finding has a weakness, namely, the coefficient of determination is low only 9.9 percent so the statistical result on this research is not able to generalize general results on the timeliness of financial reporting Contribution: This study is useful in highlighting the timeliness of financial reporting should focus to aid in decision making by users and to avoid a company risk.